Avaliação da habilidade de leitura de crianças do ensino fundamental: medidas direta e indireta - Douglas de Araujo Vilhena (2015)
The dissertation consists of three articles interconecter. The first describes the process of adaptation of the French Lobrots Lecture 3 test, renamed to Reading Performance Screening Test (Teste de Desempenho de Leitura TDL). As a continuation, the second article presents the psychometric validation and standardization of TDL. The third, reports structural changes made in the Scale of Evaluation of Reading Competence by the Teacher (Escala de Avaliação da Competência em Leitura pelo Professor EACOL), with subsequent validation and standardization of instrument. The adaptation of the TDL started due to the demand of a test to assess the silent reading of elementary school children to provide concurrent validation for the silent reading subscale of EACOL. Data were collected from 484 children 7-to-11 years (2nd-to-5th school year) between November and December 2013, by seven instruments to evaluate reading, general cognition and social behavior. Both the TDL and the EACOL showed to be robust instruments in the assessment of reading competence of schoolchildren, helping researchers and clinicians to quick detect students with low and high academic performance.